An Analytical Framework of Environmental Issues - Levin, Jonathan (Washington, D.C. : International Monetary Fund, 1993)
Environmental effects which were insignificant in the past, when the fewer concentrations of population or products of modern technology allowed the vast absorptive capacity of nature to act as a sink, are quite evident today--in the pollution of air or water, the overuse of potentially renewable fishing or forestry resources, or the wasteful extraction of nonrenewable, mineral, resources. To contribute to an overall understanding of environmental issues, this paper sets out a general analytical framework encompassing the physical character of environmental problems, the behavioral factors that contribute to them, and the principal approaches to their prevention and correction.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet